Uji kandungan nutrisi nugget daging domba dengan pemanfaatan daun kelor - Asmaq, Nur; Warsito, Kabul; Matondang, Syaiful Nasri; Suhut, Anwar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
This research aimed to determine the effect of adding Moringa oleifera leaves on the nutritional value of lamb nuggets. Moringa leaves (Moringa oleifera) is a tropical plant that can quickly grow in low areas such as North Sumatra. This plant contains anticancer and antioxidants, which can be used as a natural ingredient to maintain and improve the quality of lamb nuggets. In this research, Moringa leaves and lamb were processed into nuggets. This research used an experimental method with a completely randomised design with 4 treatments and 4 replications. This research showed that adding Moringa leaves showed a very significant difference (P<0.01) in the water content, pH value and total bacterial colony test.